Suppression of Breast Cancer Metastasis Using Stapled Peptides Targeting the WASF Regulatory Complex. (15th June 2017) - Cowell, John K; Teng, Yong; Bendzunas, N George; Ara, Roxan; Arbab, Ali S; Kennedy, Eileen J
The WASF3 gene facilitates the metastatic phenotype, and its inactivation leads to suppression of invasion and metastasis regardless of the genetic background of the cancer cell. This reliance on WASF3 to facilitate metastasis suggests that targeting its function could serve as an effective strategy to suppress metastasis. WASF3 stability and function are regulated by the WASF Regulatory Complex (WRC) of proteins, particularly CYFIP1 and NCKAP1. Knockdown of these proteins in vitro leads to disruption of the WRC and suppression of invasion. We have used mouse xenograft models of breast cancer metastasis to assess whether targeting the WRC complex suppresses metastasis in vivo. Stapled peptides targeting the WASF3-CYFIP1 interface (WAHM1) and the CYFIP1-NCKAP1 interface (WANT3) suppress the development of lung and liver metastases. Targeting these critical protein-protein interactions, therefore, could potentially be developed into a therapeutic strategy to control cancer cell invasion and metastasis.